American Shooter : A Personal History of Gun Culture in the United States - Souter, Gerry (Book collections on Project MUSE., 2012)
Provides a history of firearm ownership in the United States, from the use of muskets by early settlers at Jamestown to the purchase of guns today, and offers the author's take on gun culture through personal anecdotes.